A Review on Microfluidic Platforms Applied to Nerve Regeneration - Chuankai Dai; Xiaoming Liu; Rongyu Tang; Jiping He; Tatsuo Arai (Applied Sciences, 2022)
In recent decades, microfluidics have significantly advanced nerve regeneration research. Microfluidic devices can provide an accurate simulation of in vivo microenvironment for different research purposes such as analyzing myelin growth inhibitory factors, screening drugs, assessing nerve growth factors, and exploring mechanisms of neural injury and regeneration. The microfluidic platform offers technical supports for nerve regeneration that enable precise spatio-temporal control of cells, such as neuron isolation, single-cell manipulation, neural patterning, and axon guidance. In this paper, we review the development and recent advances of microfluidic platforms for nerve regeneration research.